Educational Management Model for Transforming Islamic Religious Education in the Digital Era: Integrating Religious Literacy and 21st-Century Competencies - Kuswadi, Ali; Feri Riski Dinata; Ermayanti; Dwi Novianti; Moh. Solikul Hadi (Scidac Plus, 2026)
The rapid digital transformation in Indonesia has significantly reshaped the landscape of Islamic Religious Education (IRE) across primary and secondary schools. The integration of digital platforms, artificial intelligence, and online learning environments has altered how religious knowledge is accessed, interpreted, and internalized by students. This study aims to analyze the transformation of Islamic Religious Education in the digital era through the development of an integrative model that combines religious literacy and 21st century competencies. Employing a qualitative multi site case study design, this research was conducted in selected Islamic junior and senior secondary schools in Indonesia. Data were collected through in depth interviews, classroom observations, and document analysis. The findings reveal three major transformations: (1) the shift from teacher centered doctrinal transmission to interactive digital learning; (2) the redefinition of religious literacy from textual understanding to critical contextual interpretation; and (3) the integration of collaboration, critical thinking, communication, and digital ethics into Islamic learning. The study proposes an integrative model of Islamic Religious Education that aligns theological depth with digital era competencies. The research contributes to the theoretical reconstruction of Islamic education by positioning religious literacy as a strategic axis in navigating digital disruption while maintaining normative Islamic values.